MAQASHID SHARIA INDEX AS A TOOL TO EVALUATE THE SOCIAL PERFORMANCE OF COMPANIES LISTED IN JAKARTA ISLAMIC INDEX - Fauziah, Ulfah Nurul; Kristianingsih, Kristianingsih (Jurnal Ekonomi dan Bisnis Terapan, 2018)
This study aims to develop a new approach to evaluate social performance by adding several variables, that an aspect of the achievement of sharia objectives (Maqasid al-Shariah) and to know how company social performance using the developed approach. Social performance in concept of Islam has a difference when compared with social performance in general because it embracing the taqwa in every aspect, where the company assumes their role as servants and khalifah of Allah Based on this difference of meaning is required assessment or evaluation of the performance of Islamic institutions Different from the performance evaluation in general to realize the aspirations of Islamic moral economy. This research method uses descriptive quantitative. Quantitative is used to calculate each ratio and this descriptive research to explain Maqasid Shariah index developed. This study uses the purpose of Maqasid Shariah as research variable. The objectives of the Maqasid Shariah are safeguarding of value of human life, safeguarding of human self, safeguarding of value of social and safeguarding of value of the physical environment. Calculation method using Simple Additive Weighted and Structural Equation Modelling. The results of this study are the index to evaluate the company social performance based on Maqasid Shariah value and based on the measurement using Maqasid Shariah index, company social performance in this study below average value. In this research PT. Timah occupies the best social performance of all companies studied followed by PT. Jasa Marga in the lowest